How can team synchronisation tendencies be developed combining Constraint-led and Step-Game approaches? An action-research study implemented over a competitive volleyball season - Ramos, A.; Coutinho, P.; Ribeiro, J.; Fernandes, O.; Davids, K.; Mesquita, I. (European Journal of Sport Science, 2022)
Combining Constraint-led (ecological) and Step-Game (constructivist) approaches through an Action-Research (AR) design conducted throughout a competitive volleyball season, this study aimed to: (i) analyse the impact of increased tactical complexity on lateral and longitudinal collective synchronisation tendencies during defensive and offensive counterattack-subphases, and (ii) examine how opposition attacking contexts (i.e., playing in full-system or in-system) might influence synchronisation tendencies throughout each counterattack-subphase. Performance of a youth team, comprised of fifteen players, was studied across three AR-cycles. The team`s competitive performance was analysed through three competitive matches (one per cycle). Team synchronisation tendencies were evaluated using the cluster-phase method and a 3 (matches) x 2 (counterattack-subphases) x 2 (opposition attacking contexts) x 2 (court directions) repeated-measures ANOVA were used to calculate the differences in cluster-amplitude mean values. Results showed that increments in tactical complexity (second AR-cycle) were followed by decreases in collective synchronisation tendencies, which were (re)achieved during the third AR-cycle, possibly due to the ecological-constructivist coaching intervention. Our findings imply that coaches could design representative and specific-didactical learning environments, predicated on a team`s tactical needs and strategical ideas from a game-plan, framing player intentionality. Results also support the use of questioning strategies to narrow players` attentional focus, stimulating perceptual attunement to relevant constraints emerging in performance. Finally, the insider AR-design provided valuable contextualised insights on coaching interventions for developing collective coordinative structures.